Incremental changes in QRS duration as predictor for cardiovascular disease: a 21-year follow-up of a randomly selected general population - Xiaojing Chen (Nature Portfolio, 2021)
Abstract The QRS complex has been shown to be a prognostic marker in coronary artery disease. However, the changes in QRS duration over time, and its predictive value for cardiovascular disease in the general population is poorly studied. So we aimed to explore if increased QRS duration from the age of 50–60 is associated with increased risk of major cardiovascular events during a further follow-up to age 71. A random population sample of 798 men born in 1943 were examined in 1993 at 50 years of age, and re-examined in 2003 at age 60 and 2014 at age 71. Participants who developed cardiovascular disease before the re-examination in 2003 (n = 86) or missing value of QRS duration in 2003 (n = 127) were excluded. ΔQRS was defined as increase in QRS duration from age 50 to 60. Participants were divided into three groups: group 1: ΔQRS < 4 ms, group 2: 4 ms ≤ ΔQRS < 8 ms, group 3: ΔQRS ≥ 8 ms. Endpoints were major cardiovascular events. And we found compared with men in group 1 (ΔQRS < 4 ms), men with ΔQRS ≥ 8 ms had a 56% increased risk of MACE during follow-up to 71 years of age after adjusted for BMI, systolic blood pressure, smoking, hyperlipidemia, diabetes and heart rate in a multivariable Cox regression analysis (HR 1.56, 95% CI:1.07–2.27, P = 0.022). In conclusion, in this longitudinal follow-up over a decade QRS duration increased in almost two out of three men between age 50 and 60 and the increased QRS duration in middle age is an independent predictor of major cardiovascular events.